2021
DOI: 10.2147/hiv.s282928
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Six-Month Appointment Spacing Model Utilization Among ART Clients in the Public Health Facilities of Jimma Town, Southwest Ethiopia: Case–Control Study

Abstract: Background Ethiopia is currently implementing an Appointment Spacing Model (ASM) for ART. A study conducted in 6 hospitals that piloted ASM showed that 51% of eligible clients declined ASM. Studies conducted on ASM have focused on its benefits, not factors determining its utilization. This study aimed to identify determinants of ASM non-utilization. Objective To identify determinants of ASM non-utilization among stable ART clients. Methods An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Uptake of ASM. Eligible ART clients who fulfill the World Health Organization's (WHO) criteria of stable adult clients accepting the six months schedule for both clinical evaluation and medication refill were categorized as 'uptake' and coded as "1" whereas those who refused to be enrolled in ASM were categorized as 'non-uptake' and coded as "0" [6].…”
Section: Definition Of Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Uptake of ASM. Eligible ART clients who fulfill the World Health Organization's (WHO) criteria of stable adult clients accepting the six months schedule for both clinical evaluation and medication refill were categorized as 'uptake' and coded as "1" whereas those who refused to be enrolled in ASM were categorized as 'non-uptake' and coded as "0" [6].…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…Although Ethiopia is close to reaching HIV epidemic control [4], treatment failure remains a major challenge due to discontinuation of ART, and poor ART adherence. Furthermore, patients endure long traveling distances, high transportation costs, long waiting times to get ART service, persistent HIV-related stigma and discrimination, poor attitudes by healthcare workers, and high caseloads within ART facilities which contribute to overall poor ART service in Ethiopia [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that younger age was associated with a lower likelihood of being on ≥3MMD and higher risk of switching from ≥3MMD to <3MMD may reflect differences in client's preferences or bias/perceptions from healthcare workers. Previous research has found that some adult clients may prefer standard clinical care rather than MMD due to the ongoing support and counseling and fear of HIV stigma and discrimination due to the challenges to safely and privately storing MMD [17] or due to misunderstanding about MMD or mistrust in the health system. While this is plausible, young adults may also face stigma and discrimination while accessing HIV services [18], which could have impacted access and continuation of MMD.…”
Section: Discussionmentioning
confidence: 99%
“…Other service delivery models, for example six‐monthly appointments with reduced frequency of clinic visits by increasing months between ART refills may reduce patient‐incurred costs further. However, preference for this model still varies showing the complexity of preferences [42‐44].…”
Section: Discussionmentioning
confidence: 99%